2009
DOI: 10.1093/carcin/bgp102
|View full text |Cite
|
Sign up to set email alerts
|

CYP450 polymorphisms as risk factors for early-onset lung cancer: gender-specific differences

Abstract: Cytochrome P450 (CYP) enzymes, involved in metabolism of tobacco carcinogens, are also involved in estrogen metabolism and many are regulated by estrogens. These genes may thus be of relevance to gender-specific differences in lung cancer risk, particularly in early-onset lung cancer, where a high proportion of women is observed. We conducted a case-control study to investigate genetic polymorphisms in cytochromes that might modify the risk of developing early-onset lung cancer. In total, 638 Caucasian patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 49 publications
2
56
1
3
Order By: Relevance
“…Seven studies included enough information in a subgroup analysis by smoking status. 14,15,[18][19][20][21][22] The distribution of genotypes in the controls was consistent with Hardy-Weinberg equilibrium in all studies. All the cases were pathologically confirmed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Seven studies included enough information in a subgroup analysis by smoking status. 14,15,[18][19][20][21][22] The distribution of genotypes in the controls was consistent with Hardy-Weinberg equilibrium in all studies. All the cases were pathologically confirmed.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have studied the interaction or joint effect of CYP1B1 Leu432Val polymorphism and smoking status on lung cancer. 14,15,18,19,22 In the present meta-analysis, we found that CYP1B1 Leu432Val polymorphism had an increased lung cancer risk in smokers. It is possible that individuals with CYP1B1 Leu432Val polymorphism were more susceptible to smoking-related lung cancer when being exposed to higher level of tobacco smoke.…”
Section: Discussionmentioning
confidence: 46%
“…In addition to xenobiotic metabolism, CYP1B1 is also known to play a role in estrogen metabolism, and may contribute to differential susceptibility by sex toward smoking-related diseases. Genetic polymorphisms in CYP1B1 have been associated with an increased risk of lung cancer and early menopause in women; notably, interactions between singlenucleotide polymorphisms in CYP1B1 and smoking history appear to increase the risk of both of these outcomes (29)(30)(31). The differential correlations by sex between methylation at CYP1B1 and lung function and radiographic emphysema reported in our study warrant further investigation.…”
Section: Discussionmentioning
confidence: 54%
“…There are two studies demonstrating a significantly increased risk of LC overall for carriers of the minor allele of CYP1B1 SNP rs1056836 among women and black ever-smoking women by Timofeeva et al [14] and Cote et al [15], respectively. However, other studies have failed to find any appreciable correlation between the CYP1B1 Leu432Val polymorphism and LC risk [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%